Kinerja Training Kit Mesin Pengisi dan Penutup Botol otomatis Sebagai Media Praktik Programmable Logic Controllers di SMK - Sukir Sukir; Tangguh Wicaksono (Departement of Mathematics Education, 2023)
This research aims to: (1) develop a prototype of an automatic bottle filling and capping machine training kit as a Programmable Logic Controllers (PLC) practice tool in vocational high schools (SMK), and (2) assess the performance of the automatic bottle filling and capping machine training kit as a PLC practice tool in SMK. This research adopts the research and development methodology in the field of education. The development model used is the ADDIE model by Robert Maribe Branch. The research consists of the following stages: Analyze, Design, Develop, Implement, and Evaluate. The data collection techniques employed in this study are interviews and questionnaires, using interview guides and questionnaires as instruments. The data obtained were analyzed descriptively. The results of the research indicate that: (1) a training kit for an automatic bottle filling and capping machine has been developed, which consists of main components such as the Conveyor Unit, Water Filling Unit, Water Capping Unit, OMRON CP1E N40 PLC Unit, Training Kit Components Unit, and Input/Output Terminal Block. This training kit serves as a PLC practice tool in SMK; and (2) the automatic bottle filling and capping machine training kit exhibits good performance, as demonstrated by the testing of 43 components, all of which functioned properly. The functional testing conducted under Initial Condition, Watertank Condition, Run Cycle Condition, Stop Condition, and Emergency Condition showed that all components (100%) performed well.